Patterns of acute poisoning cases at a high-altitude tertiary hospital in Nepal: a descriptive cross-sectional study - Khapung, Robin; Basnyat, Subi; Thapa, Nabin; Luitel, Bipin; Dhami, Lalit Singh; Thapa, Anita; Pandey, Alan; Adhikari, Apil; Giri, Praveen Kumar; Bhattarai, Ramesh; Bhandari, Jeetendra; Limbu, Posan Samser; et al. (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Poisoning, whether intentional or accidental, remains a significant public health issue in rural, high-altitude regions, with limited epidemiological data. Nepal, an agriculture-dependent country, sees rising pesticide-related poisonings, especially organophosphates. This study aimed to assess the prevalence, demographics, toxic agents, and intent of poisoning cases admitted to Karnali Institute of Health Sciences’ emergency department from 2019 to 2024. Methods: A retrospective study reviewed five years of poisoning cases from hospital records using census sampling. It collected demographic data, toxic agents, and intent (suicidal or accidental). Incomplete records were excluded. Data were analyzed with SPSS, using descriptive statistics like frequency, percentage, and cross-tabulations.Results: Out of 164 cases, the majority were young adults aged 15–25 years (45.1%). Females accounted for 72.6% of cases, with married females being the most affected (45.7%). Suicidal poisoning (73.2%) was more frequent than accidental poisoning (26.8%). The most frequent toxic agents were zinc phosphide (42.7%) andorganophosphates (14.6%). Herbal poisonings (including Coriaria nepalensis, Aconitum ferox, and Arisaema spp.) comprised 8.53% of the cases. Suicidal intent was highest among young adults (86.5%) and lowest in children aged 0- 14 years (19.2%). Conclusion: Young married females are at highest risk of suicidal poisoning in this Nepal region, due to frequent pesticide and herbal toxin exposure. This highlights the need for mental health programs, pesticide regulation, and community education. More studies are needed to assess prevention and long-term outcomes.